(untitled) (Investigación en Enfermería: Imagen y Desarrollo, 2019)
Being admitted to a hospital, preparing for discharge, receiving a chronic illness diagnosis, transferring from intensive care to regular care, moving to a nursing home, receiving a grave diagnosis, losing a family member, facing an environmental disaster, graduating and starting a new professional position—all of these scenarios may appear different, but ask yourself, what might they all have in common? They are all changes that trigger a transition process [Fragmento de texto].